Effect of Individual Characteristics, Work Placement and Work Environment on Employee Performance (Case Study on PT Post Energy Indonesia Jakarta Office) - Suryanto, Suryanto; Sandra, Jana (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine the effect of individual characteristics, work placement and work environment on employee performance. There are three independent variables, namely individual characteristics, work placement and work environment to be tested for the effect on the dependent variable, namely employee performance. The population in this study were all employees of PT Post Energy Indonesia Jakarta Office, amounting to 114 people. In this study using simple random sampling and obtained data as many as 57 respondents. The research data used is primary data, which is obtained through the distribution of questionnaires. The analytical tool used is multiple linear regression test. The results showed that: There is a positive and significant influence between Individual Characteristics and Work Environment on Employee Performance, but there is no effect of Work Placement on Employee Performance with a significant value. The results of the coefficient of determination test show that the Adjusted R Square value of 40% of the dependent variable on employee performance can be explained by the independent variables, namely individual characteristics, work placement and work environment, while other factors of 60% are influenced by other variables outside the variables studied.